PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS UNTUK MENGETAHUI KONDISI KEUANGAN YANG BERDAMPAK TERHADAP PREDIKSI FINANCIAL DISTRESS PADA PT BAKRIE & BROTHERS, TBK DAN ANAK PERUSAHAAN - Simamora, Patar; Haerudin, Muhamad (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2014)
ABSTRACTFinancial distress is a condition experienced by the company caused by severalfactors, namely liquidity, solvency, and profitability. This study was conducted to determinethe effect of liquidity, solvency, and profitability of the financial distress prediction inPT.Bakrie & Brothers, Tbk and subsidiaries as a result of inability of the company to pay offdebt and suffered losses several times in the period 2003-2012. The results showed liquidity,solvency, and profitability in poor condition. This condition is reinforced by the results of theanalysis by using EVA, MVA, and Zâ-Scores methods. Hypothesis testing using the F testshows F count > F table (8,583 > 2,866) means liqudity, solvency, and profitabilitysimultaneously affect the prediction of finacial distress. While testing the hypothesis using thet test showed the value of the current ratio (2,359 > 2,028) and debt to total assets ratio(4,730 > 2,028) where t count > t table which means the effect on the interest covarege ratio,meanwhile for the return on invesment ât count < -t table (-1,150 < -2,028), which meansaffect too the interest covarage ratio.Keywords : Liquidty, Solvency, Profitability, Financial Distress, Current Ratio, Debt ToTotal Assets Ratio, Return On Invesment, Interest Covarage Ratio.